Spectroscopic investigation of a new hybrid glass formed by the interaction between croconate ion and calcium polyphosphate - de Oliveira, CIR; de Oliveira, LFC; Dias, F. A.; Messaddeq, Younes [UNESP]; Ribeiro, SJL (Elsevier B.V., 2005)
In this work, a new organic-inorganic hybrid material has been synthesized by the incorporation of croconate ion into a calcium polyphosphate coacervate. The hybrid so obtained was characterized by means of electronic and vibrational spectroscopies. The material is a homogeneous mixture described by a structural model, which includes helical chains of polyphosphate ions, where the calcium ion occupies the internal vacancies of the structure. The croconate ion appears to be occupying the regions outside the polymeric structure, surrounded by several water molecules. The electronic spectrum of the incorporated material shows a broad band peaking at the same wavelength region (363 nm) observed for the aqueous solution of croconate ion, and manifesting the Jahn-Teller effect as evidenced by the doublet structure of the band. The infrared spectrum is widely dominated by the absorption bands of the polyphosphate ion and the appearance of the carbonyl stretching band at ca. 1550 cm(-1) indicates the presence of croconate ion incorporated in the structure. The Raman spectrum of the material shows several vibrational bands related to the oxocarbon moiety; most of them are shifted in comparison with the free ion. These shifts can be understood in terms of strong hydrogen bonding interactions between water molecules and the oxocarbon moiety. The low temperature methodology proposed here can be well used in the preparation of new phosphate glasses containing organic moieties opening the route to an entirely new class of hybrid glasses. (c) 2004 Elsevier B.V All rights reserved.
Keywords: croconate ion; oxocarbon ion; calcium polyphosphate coacervate; Raman spectroscopy; hybrid glasses